COSMO Study on the Heptane–Toluene–DMF/DEG-KSCN Liquid–Liquid Equilibrium System - Fernanda Bonfim de Souza, Beatriz; Lenhare, Stephanie; Cristaldo Heck, Stênio; Zuber, André; Beneti, Stéphani Caroline; Zanette, Andréia Fátima [UNESP]; Filho, Lúcio Cardozo (American Chemical Society (ACS), 2022)
The class of aromatic hydrocarbons is one of the most important in the petrochemical industry. As they are in a multicomponent mixture with aliphatics, separation represents a huge challenge given the proximity of their boiling points, and liquid–liquid extraction represents a good alternative to conventional separation processes. In this paper, liquid–liquid equilibrium data of a heptane–toluene–dimethylformamide (DMF)–diethylene glycol (DEG) system in the presence and absence of potassium thiocyanate salt were obtained and used to study solvation of ions in the DMF–DEG polar mixture solvent, using COnductor-like Screening MOdel (COSMO) modeling. It was verified that the solvation complexes failed to describe the system equilibrium despite the otherwise expected. COSMO-RS (realistic solvents) calculations of the unsolvated ions presented better approximation with experimental data compared to COSMO-SAC (segment activity coefficient) ones. The best simulation obtained with nonsolvated ions occurred probably due to π electron interactions with ion charge and hydrogen bond with the solvent.